NK Cell Levels Correlate with Disease Activity in Patients with Multiple Sclerosis on Ocrelizumab/Rituximab Therapy - Simone Dal Bello; Simone Lorenzut; Emma Saccomano; Yan Tereshko; Gian Luigi Gigli; Carlo Ennio Pucillo; Mariarosaria Valente (MDPI AG, 2024)
Background: Recently, research on the pathogenesis of multiple sclerosis (MS) has focused on the role of B lymphocytes and the possibility of using specific drugs, such as Ocrelizumab and Rituximab, directed toward these cells to reduce inflammation and to slow disease progression. Objective: We aimed to evaluate the effect of Ocrelizumab/Rituximab on laboratory immune parameters and identify the predictors of treatment responses. Methods: A retrospective single-center study was conducted among patients who received infusion therapy with an anti-CD20 drug to treat MS. Results: A total of 64 patients met the inclusion criteria, with 277 total cycles of therapy studied. Compared with the baseline values, anti-CD20 infusions resulted in absolute-value and percentage decreases in B lymphocyte levels and increased the absolute and percentage levels of NK cells 3 and 5 months after therapy (p < 0.001). After multivariate logistic regression analysis, a reduced percentage level of NK cells 3 months after infusion could predict disease activity 6 months after Ocrelizumab/Rituximab administration (p = 0.041). Conclusions: Lower percentage levels of NK cells 3 months after anti-CD20 infusion correlate with the presence of disease activity 6 months after therapy, confirming a possible protective role of NK cells in MS.